PENGAYAAN PENGELOLAAN KARANG TARUNA DI DESA CIKARAGEMAN - Herawati, Heny; Soraya, Elly; Bandawati, Euis; Lestari, Sri; Farida, Farida; Ahyar, Miftahul (Gapenas Publisher, 2023)
Karang Taruna is a forum for the younger generation to develop organizations. The lack of independence of Karang Taruna members in efforts to develop the Karang Taruna organization needs to be corrected. The Community Service activity program of the Faculty of Economics, As-Syafi'iyah Islamic University is how to develop organizational ethics, communication and activity programs within the organization. The enrichment training for Karang Taruna management in Cikarageman village was attended by 18 members of Karang Taruna in Cikarageman Village. Participants can understand well the material being taught and hope that this activity can be continued to the implementation stage in the organization they own, so that the youth organization can run well with the programs they have and can develop existing human resources in the Cikarageman Village environment